Peranan Unit Payment Collection PT. Telkom Witel Makassar dalam Meningkatkan Kualitas Pelayanan Jaringan Indihome - Harpiani, Harpiani; Kurnadipare, Aleytha Ilahnugrah; Firdausa, Farah Putri; Sukarna, Sukarna (-, 2024)
Telkom Makassar is the largest telecommunications company in Indonesia with the most popular service currently being IndiHome as a network-based facility. This service is not free but is paid through a good payment system. Payment Collection is one of the units engaged in receivables collection activities that require customers to make payments in the current month or in arrears in the previous month. PKL students are involved in the success of this Payment Collection program so that they know in detail about aspects related to Payment Collection. This paper aims to describe the role of Payment Collection in improving the service quality of IndiHome products. The method used in this activity is collaborative participatory qualitative descriptive, which is a new method used by involving oneself in the process of collecting actual and detailed information so that it can be used as an evaluation for the future. The results obtained from this activity are the process of increasing the quality of IndiHome network services at Telkom Makassar, although this increase still involves the Payment Collection unit itself. Thus, it can be concluded that the success of the Payment Collection in its role in dealing with and handling customer complaints is greatly helped by our involvement as the executor of customer service assistants for IndiHome products